Strengthening the Child’s Protection Program in the Philippines - Mobo, Froilan D. (Future Science / FSH-PH Publications, 2021)
The impact of the COVID-19 Pandemic greatly affects not only the economy but also the society because the majority of the Filipino were unemployed which makes their lives and situations more devastated. There are many reports in the Philippines that violence on child at home – predominantly those children already living in vicious or dysfunctional family situations, (Ramirez, 2020). It was also reported that during the lockdown period in March 2020, The Philippine justice agencies and child protection shareholders rescued at least 136 victims, seized 30 suspects, and found 18 convictions. The Local Government Unit with the collaborations of the Barangay must strengthen the child protection program amidst the COVID-19 Pandemic this is to reduce child victims from violence to achieve the 17 sustainability and development of the United Nations.